CREATING VALUE THROUGH KNOWLEDGE TRANSFER - Küsel, Thomas Wolfgang (My University, 2011)
Knowledge transfer is becoming an increasingly important component of the offerings produced by technology organisations. These organisations face the challenges of understanding how the transfer of knowledge creates value for their clients and how to facilitate this transfer of knowledge. The purpose of this research was to discover the components of the created value and the mechanisms which can be used to assist the transfer of knowledge. The main findings were that value is created by building the client‟s tacit knowledge about the technology and by embedding knowledge explicitly in the form of technological tools and related processes. A model for efficient knowledge transfer was developed and a case study revealed ten practical mechanisms based on this model.
MBA thesis - WBS
Keywords: Knowledge management